2006
DOI: 10.1038/sj.ijo.0803215
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and body weight change: a 20-year prospective community study of young adults

Abstract: Objective: There is increasing evidence for an association between asthma and body weight change. The objectives of these analyses were to examine the temporal relationships of this association and to explore the role of childhood depression as an explanatory factor. Methods: Data were derived from six subsequent semistructured interviews on health habits and health conditions from a single-age community study of 591 young adults followed up between ages 20 and 40 years. Results: Cross-sectionally (over the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 38 publications
4
34
1
Order By: Relevance
“…Although most previous studies documented that obesity precedes and predicts the development of asthma (4,8,22), no unanimity exists. A recent prospective study following subjects from age 20 to 40 years showed that active asthma was associated with later weight gain and later obesity among women, whereas weight gain and obesity were not associated with later asthma (12). However, no association was found among men.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although most previous studies documented that obesity precedes and predicts the development of asthma (4,8,22), no unanimity exists. A recent prospective study following subjects from age 20 to 40 years showed that active asthma was associated with later weight gain and later obesity among women, whereas weight gain and obesity were not associated with later asthma (12). However, no association was found among men.…”
Section: Discussionmentioning
confidence: 95%
“…Although longitudinal studies have documented obesity as a risk factor for asthma incidence (8)(9)(10)(11), it is unclear whether children with asthma are at higher risk for the development of obesity. Several risk factors for obesity are more prevalent among children with asthma, including reduced physical activity (12) and potential adverse effects from corticosteroid medications (13). If asthma increases the risk for developing obesity, then a portion of the obesity epidemic in children may be related to the increased occurrence of asthma or the effects of a common etiologic factor.…”
mentioning
confidence: 99%
“…C-reactive protein, leptin and adiponectin) were not investigated in this study. In addition, adolescents with higher BMI may have physiological impairments in lung function, more gastro-esophageal reflux, and sleep apnea, and thereby may be misclassified as asthmatics [10,11,32]. Future prospective studies will be necessary to clarify the relationship between obesity, inflammation and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…27). Epidemiological evidence from several studies suggests a correlation between body mass index and asthma (28)(29)(30)(31)(32). Using quantitative real time RT-PCR, Western blot analysis, and enzyme immunoassay, we found that activated Th2 cells selectively expressed the gene PMCH.…”
Section: T H1 and Th2 Cells Are The Two Main Subsets Of Cd4mentioning
confidence: 99%